2015
DOI: 10.1165/rcmb.2013-0440oc
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Epoxide Hydrolase Inhibitor Attenuates Inflammation and Airway Hyperresponsiveness in Mice

Abstract: Control of airway inflammation is critical in asthma treatment. Soluble epoxide hydrolase (sEH) has recently been demonstrated as a novel therapeutic target for treating inflammation, including lung inflammation. We hypothesized that pharmacological inhibition of sEH can modulate the inflammatory response in a murine ovalbumin (OVA) model of asthma. BALB/c mice were sensitized and exposed to OVA over 6 weeks. A sEH inhibitor (sEHI) was administered for 2 weeks. Respiratory system compliance, resistance, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 41 publications
6
59
1
Order By: Relevance
“…GSK2256294 demonstrates picomolar activity toward sEH, effectively increases in vivo EET/DHET and epoxyoctadecenoic acid/dihydroxyoctadecenoic acid ratios, and reduces cell counts of macrophages, neutrophils, and keratinocyte chemoattractant cells of smoke-exposed rodents (Podolin et al, 2013). These observations are consistent with several studies demonstrating the efficacy of sEH inhibitors at reducing inflammation and general lung injury from smoke exposure (Smith et al, 2005;Wang et al, 2012) and asthma (Yang et al, 2015).…”
Section: Developing a Path To The Clinicsupporting
confidence: 87%
“…GSK2256294 demonstrates picomolar activity toward sEH, effectively increases in vivo EET/DHET and epoxyoctadecenoic acid/dihydroxyoctadecenoic acid ratios, and reduces cell counts of macrophages, neutrophils, and keratinocyte chemoattractant cells of smoke-exposed rodents (Podolin et al, 2013). These observations are consistent with several studies demonstrating the efficacy of sEH inhibitors at reducing inflammation and general lung injury from smoke exposure (Smith et al, 2005;Wang et al, 2012) and asthma (Yang et al, 2015).…”
Section: Developing a Path To The Clinicsupporting
confidence: 87%
“…The lung vasculature is known to be a rich source of lipid mediator biosynthesis from AA, and EETs have been previously described as the predominant eicosanoids in human lungs upon stimulation with the Ca 2+ ionophore A23187 challenge (Kiss, et al, 2010). EETs in the lung are involved in many pulmonary diseases, such as asthma (Norton, et al, 2012, Yang, et al, 2015), cigarette smoke extract-induced lung injury (Yu, et al, 2015), lung ischemia-reperfusion injury (Chen, et al, 2015), and pulmonary hypertension (Revermann, et al, 2009). A recent study showed that EETs could inhibit the expression of α-SMA and TGF-β1/SMADs, protect the remnant kidney in nephrectomized rat via the inhibition of fibrosis (Zhao, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There has been great recent interest in the therapeutic potential of sEH inhibitors as novel antiinflammatories. sEH inhibitors or genetic disruption of sEH in mice reduces inflammation in models of endotoxin-induced pulmonary inflammation (22), ischemia-reperfusion injury (33,34), subarachnoid hemorrhage (35), and the murine ovalbumin model of asthma (36), and in more chronic models including atherogenic diet-induced fatty liver disease and adipose tissue (37) and atherosclerosis (38,39). In contrast, the expression and roles of epoxy-oxylipins during inflammatory resolution have not been investigated.…”
Section: Discussionmentioning
confidence: 99%